Anthropometric Measures of the Posterior Condyles: Gender Differences and Correlation to Implant Sizing - Ehmke, Thomas; Aghazadeh, Mehran; Bono, Olivia J.; Robbins, Claire; Bono, James V. (The Journal of Knee Surgery, 2019)
There is abundant data concerning morphological dimensions of the distal femur, particularly in women, which has led to redesign of the femoral component in total knee arthroplasty (TKA). Clinical experience reveals existing asymmetry of the femoral posterior condyles, yet current implant designs have a symmetrical femoral component. The objectives of this study were to analyze the dimensions of posterior condylar bone resection from a group of patients undergoing TKA and correlate the measurements to one prosthetic system. We retrospectively reviewed single surgeon morphological data from the posterior condyles of 105 knees during TKA. The study included 54 males and 51 females. Measurement of the posterior condylar bones was performed with a standard metric metal ruler by one investigator. Known dimensions of a single type of implant design were compared with the resection data. The average difference of posterior medial and lateral condylar width was 5.7 and 5.3 mm in males and females, respectively. The average host posterolateral condylar bone was 5.4 mm less than the trial implant across five sizes in both males and females. Results suggest that the dimension of the posterior lateral condyle is much smaller than the dimension of the implant in both groups of patients. Dimension of the posterior medial is close to dimension of the implant. Overhang of the component posterolaterally can create soft tissue irritation and result in postoperative pain and decreased range of motion. Our results increase awareness of the dimensions of the native posterolateral condyle and may influence future design of femoral implants used in total knee arthroplasty.
Keywords: anthropometric measurements; posterior condyle; gender; implant size